Analisis Tugas Perkembangan Siswa Melalui Instrumen Inventori Tugas Perkembangan Pada Siswa SMPN 14 Kota Serang - Intan Repita Sari; Raden Ceuceu Oceania; Rical Lavigzi; Fitri Nur Kamilah; Eko Ribawati (Universitas Palan, 2025)
This research was conducted using the Inventori Tugas Perkembangan (ITP) as a data collection tool. The reseacrh utilized the result of the Inventori Tugas Perkembangan (ITP) as an application of developmental tasks for 7th-grade studen at SMPN 14 Kota Serang. In addition, the assessment results using the Inventori Tugas Perkembangan (ITP) aimed to develop guidance and counseling programs tailored to the student’s needs. The research was carried out at SMPN 14 Kota Serang, with subjects being students from classes 7D, 7E and 7F in the 2024/2025 academic year. The research aimed to collect data and analyze the needs and difficulties faced by 7th-grade students at SMPN 14 Kota Serang. Another objective was to provide an understanding of the use and benefits of the Inventori Tugas Perkembangan (ITP) as a tool to assess student needs. This research employed a descriptive quantitative method and the Inventori Tugas Perkembangan (ITP) as the data collection instrument. The researcher will present the result obtained through the Inventori Tugas Perkembangan (ITP), This research is expected to contribute to the knowleddge base and assist counselor in providing programs and services that meet the needs of students.